The Extended Overlap Alternate Arm Converter: A Voltage-Source Converter With DC Fault Ride-Through Capability and a Compact Design - Merlin, Michael Marc Claude; Soto Sanchez, Diego Enrique; Judge, Paul Daniel; Chaffey, Geraint; Clemow, Philip; Green, Tim C.; Trainer, David R.; Dyke, Kevin J. (My University, 2018)
The alternate arm converter (AAC) was one of the first modular converter topologies to feature dc-side fault ride-through capability with only a small penalty in power efficiency. However, the simple alternation of its arm conduction periods (with an additional short overlap period) resulted in 1) substantial six-pulse ripples in the dc current waveform, 2) large dc-side filter requirements, and 3) limited operating area close to an energy sweet spot. This paper presents a new mode of operation called extended overlap (EO) based on the extension of the overlap period to 60 degrees, which facilitates a fundamental redefinition of the working principles of the AAC. The EO-AAC has its dc current path decoupled from the ac current paths, a fact allowing 1) smooth dc current waveforms, 2) elimination of dc filters, and 3) restriction lifting on the feasible operating point. Analysis of this new mode and EO-AAC design criteria are presented and subsequently verified with tests on an experimental prototype. Finally, a comparison with other modular converters demonstrates that the EO-AAC is at least as power efficient as a hybrid modular multilevel converter (MMC) (i.e., a dc fault ride-through-capable MMC), while offering a smaller converter footprint because of a reduced requirement for energy storage in the submodules and a reduced inductor volume.
Keywords: ac-dc power conversion; active filters; capacitive energy storage; hvdc transmission; power system faults; power transmission protection